Acetylation of BMAL1 by TIP60 controls BRD4-P-TEFb recruitment to circadian promoters - Petkau, Nikolai; Budak, Harun; Zhou, Xunlei; Oster, Henrik; Eichele, Gregor (eLife, 2019)
Many physiological processes exhibit circadian rhythms driven by cellular clocks composed of interlinked activating and repressing elements. To investigate temporal regulation in this molecular oscillator, we combined mouse genetic approaches and analyses of interactions of key circadian proteins with each other and with clock gene promoters. We show that transcriptional activators control BRD4-PTEFb recruitment to E-box-containing circadian promoters. During the activating phase of the circadian cycle, the lysine acetyltransferase TIP60 acetylates the transcriptional activator BMAL1 leading to recruitment of BRD4 and the pause release factor P-TEFb, followed by productive elongation of circadian transcripts. We propose that the control of BRD4-P-TEFb recruitment is a novel temporal checkpoint in the circadian clock cycle.